Development and psychometric properties of knee-specific body-perception questionnaire in people with knee osteoarthritis: The Fremantle Knee Awareness Questionnaire. - Tomohiko Nishigami; Akira Mibu; Katsuyoshi Tanaka; Yuh Yamashita; Eiji Yamada; Benedict M Wand; Mark J Catley; Tasha R Stanton; G Lorimer Moseley (PLoS ONE, 2017)
Recent systematic reviews have demonstrated that pain associated with knee osteoarthritis (OA) is a complex phenomenon that involves various contributors. People with knee OA exhibit symptoms of impaired body-perception, including reduced tactile acuity, impairments in limb laterality recognition, and degraded proprioceptive acuity. The Fremantle Back Awareness Questionnaire (FreBAQ) was developed to assess body-perception specific to the back in people with chronic low back pain. The aim of this study was to develop and assess the psychometric properties of a knee-specific version of the FreBAQ-J (FreKAQ-J), determine whether people with knee pain experience perceptual impairments and investigate the relationship between disturbed self-perception and clinical status.Sixty-five people with knee OA completed the FreKAQ-J. A subset of the participants completed the FreKAQ-J again two-weeks later. Rasch analysis was used to assess item order, targeting, category ordering, unidimensionality, person fit, internal consistency, and differential item functioning. Validity was investigated by examining the relationship between the FreKAQ-J and clinical valuables.The FreKAQ-J had acceptable internal consistency, unidimensionality, good test-retest reliability, and was functional on the category rating scale. The FreKAQ-J was significantly correlated with pain in motion, disability, pain-related catastrophizing, fear of movement, and anxiety symptomatology.We developed FreKAQ-J by modifying the FreBAQ-J. The FreKAQ-J fits the Rasch measurement model well and is suitable for use in people with knee OA. Altered body perception may be worth evaluating when managing people with knee OA.